Critique of materials‐based models of ductile machining in brittle solids. Issue 11 (7th July 2020) - Huang, Han; Lawn, Brian R.; Cook, Robert F.; Marshall, David B.
Abstract: Indentation fracture models of ductile machining in hard and brittle materials are critically appraised. Relations obtained in a seminal study for critical depths of cut below which fracture is suppressed are examined and amended. Limitations inherent in any such materials‐based analysis, in addition to uncertainties in empirical measurements of underpinning mechanical properties (modulus, hardness, toughness) and of threshold grinding depths, suggest that caution should be exercised in unconditional usage. Notwithstanding these limitations, the value of the indentation fracture methodology in placing ductile machining on a sound materials science footing is maintained.